Talent management and organizational citizenship behaviour: A study at private higher learning institution in Sabah - Dayang Fauziah Kadir (2007)
This study aims to examine the relationship between talent management factors (skill development and perceived organizational support) and organizational citizenship behaviour at the Private Higher Learning Institution in Kota Kinabalu, Sabah. Through this paper also, both academic researcher and organization may be able to discover the significant effect of talent management factors (skill development and perceived organizational support) and organizational citizenship behaviour in order to improve the performance of the organization and thus survive in the competitive market. There are 128 respondents who have given cooperation in providing the data needed by the researcher to accomplish this study. Then, the data have been analyzed by using SPSS program such as reliability analysis, multiple regression and etc. Through the analysis result, the hypotheses testing, which involved the relationship between skill development and organizational citizenship behaviour and also perceived organizational support and organizational citizenship behaviour are significant. The study suggests that the employers need to highly emphasize on the skill development and organization support to promote organizational citizenship behaviour in the organization to achieve their vision and mission.